Hepatozoon canis infection associated with dog ticks of rural areas of Rio de Janeiro State, Brazil - O'Dwyer, L. H.; Massard, C. L.; de Souza, JCP (Elsevier B.V., 2001)
Hepatozoon canis is a tick-borne protozoan that infects dogs and has been reported throughout the world. Manifestation of H. canis infection varies from being sub-clinical in apparently healthy dogs to severe illness. The main vector of the infection is the dog tick, Rhipicephalus sanguineus although other species may also transmit this agent. H. canis has been reported previously in Brazil, but mostly as an occasional finding during laboratory exams and always associated with other diseases. The prevalence of H. canis in dogs of rural areas of Brazil has been little studied. For this study, 250 dogs from seven counties of Rio de Janeiro state were examined. All the dogs were from rural areas, near forest. of the dogs examined, 26 dogs were from Seropedica, 82 from Itaguai, 41 from Paracambi, 26 from Mangaratiba, 32 from Barra do Pirai, 32 from Pirai and 11 from Miguel Pereira. Blood smears from the peripheral blood of the ear were taken and ticks found on the dogs were collected for identification in the laboratory. Using blood smear evaluation, H. canis was identified in 39.2% of the animals examined. Other hemoparasites identified were Babesia canis (5.2%) and Ehrlichia canis (4.8%). Four tick species were found parasitizing the dogs: Amblyomma cajennense (23.6%), R. sanguineus (12.4%), Amblyomma aureolatum (2.8%) and Amblyomma ovale (2.0%). There was a positive correlation between the presence of A. cajennense and H. canis infection. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Hepatozoon canis; hemoparasites; dogs; ticks; Amblyomma cajennense